2011
DOI: 10.1016/j.apenergy.2011.03.012
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitation as a strategy for increasing starch accumulation in microalgae

Abstract: a b s t r a c tIncreasing microalgal starch content by nutrient limitation has been regarded as an affordable approach for the production of third generation bioethanol. This work evaluated starch accumulation in Chlorella vulgaris P12 under different initial concentrations of nitrogen (0-2.2 g urea L À1 ) and iron (0-0.08 g FeNa-EDTA L À1 ) sources, using a central composite design (CCD) for two factors. The obtained model: Starch content (%) = 8.220 À 16.133X 1 + 13.850X 2 1 , relating starch accumulation in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
136
0
15

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 344 publications
(156 citation statements)
references
References 23 publications
5
136
0
15
Order By: Relevance
“…The inverse relation between energy-rich compound (carbohydrate and lipid) accumulation and cell growth has been recorded in many other microalgae (Brányiková et al 2011;Li et al 2008;Wang et al 2010) and is a challenge in the economic production of microalgal biofuel feedstock (Markou et al 2012a). Several strategies, such as "two-stage" cultivation (Dragone et al 2011;Rodolfi et al 2009) or limited nutrient addition (Aikawa et al 2012;Markou et al 2012b), have been employed to solve this problem. Our results showed that unlike starch content and starch productivity, the starch and biomass concentration in the -P culture were comparable to or exceeded those in the -N and -S cultures, suggesting that extracellular phosphorus deprivation might serve as an alternative strategy if the cultivation is targeted to overall biomass and starch production.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The inverse relation between energy-rich compound (carbohydrate and lipid) accumulation and cell growth has been recorded in many other microalgae (Brányiková et al 2011;Li et al 2008;Wang et al 2010) and is a challenge in the economic production of microalgal biofuel feedstock (Markou et al 2012a). Several strategies, such as "two-stage" cultivation (Dragone et al 2011;Rodolfi et al 2009) or limited nutrient addition (Aikawa et al 2012;Markou et al 2012b), have been employed to solve this problem. Our results showed that unlike starch content and starch productivity, the starch and biomass concentration in the -P culture were comparable to or exceeded those in the -N and -S cultures, suggesting that extracellular phosphorus deprivation might serve as an alternative strategy if the cultivation is targeted to overall biomass and starch production.…”
Section: Discussionmentioning
confidence: 99%
“…Macroelement (nitrogen, sulfur, or phosphorus) limitation is the most widely explored strategy for the enhancement of starch accumulation (Ball et al 1990;Brányiková et al 2011;Dragone et al 2011). Phosphorus is an essential macroelement that is mainly incorporated into nucleic acid and phospholipids.…”
Section: Introductionmentioning
confidence: 99%
“…Estudos recentes têm demonstrado que algumas espécies microbianas, tais como leveduras, fungos, e microalgas podem ser usadas como matérias primas potenciais para a produção de biodiesel e bioetanol, devido à capacidade das mesmas de armazenar grandes quantidades de lipídios e carboidratos na sua biomassa (CHISTI, 2008;DRAGONE et al, 2011;TSIGIE et al, 2013). A maioria dos estudos é em relação à produção de biocombustíveis de microalgas (CHISTI, 2008;DRAGONE et al, 2011;YEH;CHANG, 2011;RISMANI et al, 2011.…”
Section: Microalgas Como Matéria Prima Para a Produção De Bioetanolunclassified
“…A maioria dos estudos é em relação à produção de biocombustíveis de microalgas (CHISTI, 2008;DRAGONE et al, 2011;YEH;CHANG, 2011;RISMANI et al, 2011. Margarites (2014), em experimentos de produção de etanol a partir de biomassa de Spirulina sp., apresentou produtividade de 1,18 g.L -1 .h -1 de etanol, utilizando 50% dos carboidratos provindos da sacarificação da biomassa e 50% a partir da glicose.…”
Section: Microalgas Como Matéria Prima Para a Produção De Bioetanolunclassified
“…GRIS et al (2013) reported a relationship between NaNO3 concentration and lipid content of N. oculata was inversely proportional, as well as they obtained a maximum lipid content around 30%. DRAGONE et al (2011) argued that the nutrient limitation in the culture medium causes the starch to rise and may become feasible the production of bioethanol. CHIU et al (2009) reported that the production of biofuels from microalgae depends on the growth rate of the cultured species and the oil content therein.…”
Section: Introductionmentioning
confidence: 99%